Hubungan Kerawanan Pangan Rumah Tangga, Keragaman Pangan, dan Stunting pada Anak di Indonesia: Literature Review - Devi Trisna Ramadhani (HB PRESS, 2025)
Household food insecurity in Indonesia is a significant public health issue and a root cause of malnutrition. This research aims to systematically examine the relationship between household food insecurity, dietary diversity, and stunting. This review was conducted following the PRISMA (Preferred Reporting Items for Systematic Review and Meta-Analyses) recommendations. A literature search was performed on the following databases: PubMed, ScienceDirect, MDPI, and Garuda Kemendikbud. The study focused on research conducted in Indonesia concerning household food insecurity, dietary diversity, and stunting, published between 2014 and 2023. Of the 635 original articles identified, only 9 met the criteria for this review. Five of the nine articles indicated that the Household Food Insecurity Access Scale (HFIAS) unsafe was associated with a higher prevalence of stunting, and four of the nine articles showed that low dietary diversity was related to a higher prevalence of stunting. The findings suggest that strengthening household food security and increasing dietary diversity are crucial steps to reducing stunting in Indonesia.